Identification and functional characterization of ORF19.5274, a novel gene involved in both azoles susceptibility and hypha development in Candida albicans - Huang, Mingjiao; Yang, Longbing; Zhou, Luoxiong; Sun, Chaoqin; Zhao, Wenjing; Peng, Jian; Jiao, Zhenlong; Tian, Chunren; Guo, Guo (Frontiers in Microbiology, 2022)
Azole resistance is increasingly serious due to frequent recurrence of fungal infection and long-term clinical prevention. In our previous study, we analyzed C. albicans after fluconazole (FLC) treatment and discovered the transcription factor (TF) ORF19.5274 with unknown function by TMTTM quantitative proteomics technology. we constructed the target gene deletion strain using CRISPR-Cas9 gene editing technology to determine whether in C. albicans ORF19.5274 could regulate azole sensitivity. The present data showed that ORF19.5274 gene was involved in the hypha development and susceptibility to antifungal azoles. The hyphal development was inhibited and the expression of Hwp1p (hyphal-specific gene) and other genes related to ergosterol synthesis pathway was down-regulated in C. albicans after biallelic deletion. Moreover, DCFH-DA and PI staining assays showed increased endogenous ROS levels, membrane permeability, and decreased metabolic activity of biofilm in orf19.5274Δ/Δ mutant following treatment with FLC in comparison with either SC5314 or orf19.5274Δ/Δ::ORF19.5274 strains. More importantly, orf19.5274Δ/Δ mutant significantly enhanced the efficacy of FLC against the models of G. mellonella larvae infected with C. albicans, and the above characteristics were fully or partially restored in the complementary strain, indicating that the changes caused by the gene deletion were specific. In summary, the ORF19.5274 gene is required for the hypha development of C. albicans, and is correlated with the sensitivity response to antifungal azoles in vitro and in vivo. The identification of ORF19.5275 is promising to expand the potential candidate targets for azoles.